Tripartismo e descentralização na Política de Emprego, Trabalho e Renda: estudo de caso do Rio de Janeiro - Silva, Vânia Souza da (2001)
Intends to analyse the Brazilian tripartite, paritarian and de-centralized model that manages the resources of FAT (Fundo de Amparo ao Trabalhador - Workers Protection Fund) in the employment public system of Rio de Janeiro. To reach the proposed objective, the first chapter begins with a discussion on the corporativism in Brazil, its configuration and the determinants that permitted changes in its arrangements throughout Brazilian trade-union history. In the second chapter is presented the Brazilian employment public system, and the programs and plans that forms it, and its structural characteristics; at the end, a discussion is made about why the employment system is considered as being an hibrid corporative structure. The third chapter presents how is structured the Rio de Janeiro State Employment Comission nowadays, its history and main decisions and programs, and then verifies how is ocurring the representation of political interests in the Rio de Janeiro employment system, how the politics is being integrated to the programs, and to which extension the de-centralization is ocurring according to the legal presumptions of the public politic. At the end, the analisys is concluded by some considerations that try to resume the conclusions raised by the proposed reflection.